Respostas
respondido por:
54
7² + 2.[(3 + 1)² - 4 . 1³ ] =
7² + 2.[ (4)² - 4 . 1³ ]=
7² + 2. [ 16 - 4 . 1 ] =
7² + 2.[ 16 - 4] =
7² + 2.[ 12] =
7² + 24 =
49 + 24 = 73
Bons estudos..(;
7² + 2.[ (4)² - 4 . 1³ ]=
7² + 2. [ 16 - 4 . 1 ] =
7² + 2.[ 16 - 4] =
7² + 2.[ 12] =
7² + 24 =
49 + 24 = 73
Bons estudos..(;
mafrinortepsic:
Obrigada!
respondido por:
15
Siga a ordem:
primeiro - parenteses , depois colchetes , potencias, multiplicação e por ultimo soma.
7²+ 2 .[ (4)²- 4.1] =
7²+ 2 [ 16 -4]
7² + 2 .[ 12]
49 + 24 =
73
primeiro - parenteses , depois colchetes , potencias, multiplicação e por ultimo soma.
7²+ 2 .[ (4)²- 4.1] =
7²+ 2 [ 16 -4]
7² + 2 .[ 12]
49 + 24 =
73
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás